1997
DOI: 10.1111/j.1744-9987.1997.tb00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Isovolemic Large‐Volume Erythrocytapheresis as a Rapidly Effective and Long‐Lasting Treatment Modality for Red Blood Cell Depletion in Patients with Polycythemia Vera

Abstract: Long-term survival of patients with polycythemia vera (PV) is essentially determined by the ability to reduce the risk of thromboembolic complications resulting from the altered rheological conditions by the high red blood cell (RBC) mass of these patients. RBC depletion to normal hematocrit (Hct) values is the first line therapy and should be preferred to chemotherapy (or P32) because of the long-term risk of acute leukemia or other secondary malignancies. RBC depletion is accomplished much more effectively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Isovolaemic erythropheresis has been used to reduce the RCM (Kaboth et al , 1997). To be used generally, it would have significant resource implications but it could be used acutely in the very occasional patient with an evolving ischaemic event.…”
Section: Management Of Polycythaemia Veramentioning
confidence: 99%
“…Isovolaemic erythropheresis has been used to reduce the RCM (Kaboth et al , 1997). To be used generally, it would have significant resource implications but it could be used acutely in the very occasional patient with an evolving ischaemic event.…”
Section: Management Of Polycythaemia Veramentioning
confidence: 99%
“…With TE, up to 800 ml of RBCs per single procedure can be separated from other blood components and concurrently exchanged for a substitution component hereby offering a far more efficient method in removing RBCs and iron while maintaining isovolemic conditions. In the past two decades, one randomized trial and a number of small case series have described the advantages of TE in the treatment of HH and erythrocytosis regarding efficiency, morbidity, and patient experience .…”
Section: Introductionmentioning
confidence: 99%
“…This period between two consecutive phlebotomies was dictated when hematocrit level increased to a level dangerous for the patient [ 1]. Another study reported the median treatment interval of 6–7 months by erythrocytapheresis, which was explained by the removal of more iron that led to 35–100% inhibition of in vitro growth of erythroid precursor cells that persisted for more than 25 weeks [ 6]. Other studies involving patients with hemochromatosis showed that erythrocytapheresis significantly reduced the number of phlebotomy and removed twice as much iron and RBCs when compared with manual phlebotomy [ 16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Phlebotomy is the primary method of treatment for erythrocytosis that can reduce RBC mass, improve the symptoms related to high blood viscosity, and lower the risk of thrombosis and hemorrhage [ 3–5]. Conventional phlebotomy withdraws whole blood to reduce RCM, whereas more recently developed therapeutic erythrocytapheresis (TEA) selectively removes RBCs [ 1, 6].…”
Section: Introductionmentioning
confidence: 99%